Demographic Influences on the Relationship Between Fatigue and Quality of Life in Parkinson's Disease. Issue 1 (28th October 2021) - Mantri, Sneha; Chahine, Lana M.; Nabieva, Karina; Feldman, Robert; Althouse, Andrew; Torsney, Benjamin; Albert, Steven M.; Kopil, Catherine; Marras, Connie
Abstract: Background: Fatigue has a major impact on health‐related quality of life (HR‐QOL) in Parkinson's disease (PD). Objectives: To determine whether demographic characteristics modify the relationship between fatigue and HR‐QOL. Methods: Patients with PD in the Fox Insight study completed the Parkinson Fatigue Scale (PFS‐16) and Geriatric Depression Scale (GDS‐15). Linear regression examined the relationship between the PFS‐16 and Parkinson Disease Quality of Life, as modified by age, sex, and GDS‐15. Results: A total of 1029 participants (44% female, mean age 67.4 years, and mean disease duration 4.6 years) were included in this analysis. Multivariable regression modeling demonstrated a negative effect modification for age (β = −0.07, P  < 0.001) and a positive effect modification for the GDS‐15 (β = 0.057, P  = 0.002), but not for sex (β = −0.021, P  = 0.231). Conclusion: The association between fatigue and worse HR‐QOL is greater at younger ages and in individuals with more depressive symptoms. Targeted therapeutics for these individuals may provide the greatest impact on fatigue in PD.